2004
DOI: 10.1002/dc.20007
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptor status and HER2/neu overexpression determined by automated immunostainer on routinely fixed cytologic specimens from breast carcinoma: Correlation with histologic sections determinations and diagnostic pitfalls

Abstract: Although fine-needle aspiration cytology is a routine procedure for the diagnosis of breast carcinoma, cytologic specimens have rarely been used for evaluation of hormone receptor status and HER2/neu overexpression. In order to compare the biological markers on cytology and on histology, routinely fixed smears of 110 primary breast carcinomas were immunostained for estrogen receptor (ER), progesterone receptor (PgR), and HER2/neu by automated immunostainer and the results were compared with the corresponding h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…In regard to the overall HR status, one case showed a discordant negative result, in which a few positive cells were found in the histological section. Previous studies have pointed out the intratumoral heterogeneity of positive cells as the main reason for discordant results between cytologic and histologic specimens [7,9,12,14,15] similar to the case in our results. One study suggested that the mucin over the mucinous carcinoma cells may have prevented proper immunostaining [15].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In regard to the overall HR status, one case showed a discordant negative result, in which a few positive cells were found in the histological section. Previous studies have pointed out the intratumoral heterogeneity of positive cells as the main reason for discordant results between cytologic and histologic specimens [7,9,12,14,15] similar to the case in our results. One study suggested that the mucin over the mucinous carcinoma cells may have prevented proper immunostaining [15].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have reported on assessment of the HR status using cytological specimens [6][7][8][9][10][11][12][13][14][15][16][17][18]. From the mid 1980s to the late 1990s, the HR status in cytological specimens was reported to show a good correlation with that of biochemical assays [9,11,12,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the use of cell blocks has provided material for ancillary studies including the analysis of hormone receptors (ER, PR) and HER2 status, and for immunostains (i.e. cytokeratin) that can help support the presence of metastatic carcinoma in difficult cases [5,6,7,8,9]. In addition, the effectiveness of FNA has been optimized with the use of real-time ultrasound guidance that has helped to target specific areas of concern, to confirm the needle location in the LN, and to facilitate interactions between radiologists and pathologists to improve the quality of the FNA sample [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The polysomy 17 and HER2 heterogeneity may contribute to a better understanding of HER2-positive tumours and its variation in therapeutic responses. Furthermore, this could also explain the confl icting data in studies about the prognostic and predictive role of HER2 status in breast cancer patients [23].…”
Section: Discussionmentioning
confidence: 99%